2020
DOI: 10.3892/mco.2020.1994
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of primary bone and soft tissue sarcomas in adolescents and young adults

Abstract: The aim of the present study was to investigate the clinical outcomes of adolescents and young adults with bone and soft tissue sarcomas. Records of seven male and six female patients aged 17-39 years with bone or soft tissue sarcomas were reviewed retrospectively; data on histology, size, location, grade/stage, treatment, recurrence, presence of metastasis, and prognosis were retrieved. Five-year survival rates were estimated using the Kaplan-Meier method and were compared according to age, sarcoma type, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…A Canadian registry showed that the mean operation time for sarcoma was 4 hours, and an operation time > 5 hours increased the likelihood of reoperation because of wound complications, such as infection [23]. In elderly sarcoma patients, the mean operation time is 114.7 minutes and the mean blood loss is 160.7 mL [11]. Additionally, a previous study showed that the infection rate after surgical treatment for sarcomas was 23.3% [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Canadian registry showed that the mean operation time for sarcoma was 4 hours, and an operation time > 5 hours increased the likelihood of reoperation because of wound complications, such as infection [23]. In elderly sarcoma patients, the mean operation time is 114.7 minutes and the mean blood loss is 160.7 mL [11]. Additionally, a previous study showed that the infection rate after surgical treatment for sarcomas was 23.3% [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prognosis in AYA sarcoma patients has not improved because AYA sarcoma cases are rare and we lack clinical data [10]. Recently, we described the clinical features and outcomes of AYA sarcomas in our hospital [11]. In the current study, we analyzed the data of sarcomas in AYA patients treated surgically and identified the patients that had poor prognosis to determine optimal surgical treatment approaches.…”
Section: Introductionmentioning
confidence: 98%
“…A Canadian registry showed that the mean operation time for sarcoma was 4 hours, and an operation time > 5 hours increased the likelihood of reoperation because of wound complications, such as infection [22]. In elderly sarcoma patients, the mean operation time is 114.7 minutes and the mean blood loss is 160.7 mL [11]. Additionally, a previous study showed that the infection rate after surgical treatment for sarcomas was 23.3% [23].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prognosis in AYA sarcoma patients has not improved because AYA sarcoma cases are rare, and there are not enough clinical data [10]. Recently, we described the clinical features and outcomes of AYA sarcomas in our hospital [11]. In the current study, we analyzed the data of sarcomas in AYA patients treated surgically and identified the patients that had poor prognosis to determine optimal surgical treatment approaches.…”
Section: Introductionmentioning
confidence: 98%